(untitled) (Indian Journal of Child Health, 2019)
Background: Bloodstream infections due to Candida species are becoming a major cause of morbidity and mortality in hospitalized patients. The emergence of non-albicans Candida (NACs) species with lesser susceptibility to antifungals has added to the woes of clinicians. Objectives: The objectives of the study were to determine the clinical and laboratory predictors and microbiological profile of candidemia in pediatric patients. Materials and Methods: This is a hospital-based, prospective, and cross-sectional study conducted in the pediatric department of a tertiary care hospital. A total of 250 children aged 0–12 years with risk factors for fungal sepsis were enrolled. Demographic details, clinical, and laboratory parameters were noted and samples were sent for culture. Cultures yielding growth of Candida were included in the study, and antifungal susceptibility performed. Associations were assessed using Chi-square test first and then through logistic regression models. Results: Among the 250 patients with risk factors for fungal sepsis, 47 patients (18.8%) with culture proven candidemia were identified. Predictors of candidemia among neonates were prematurity (<30 weeks), prolonged ventilation (>72 h), and thrombocytopenia. Among pediatric patients, prolonged steroid intake, Candida isolation from sites other than blood and persistent neutropenia, were significantly associated with the candidemia. NAC species were the predominant isolates (78.7%). Conclusion: Candidemia should be suspected in premature neonates requiring prolonged ventilation with unexplained thrombocytopenia. Among pediatric patients, prolonged steroid intake, Candida isolation from sites other than blood and persistent neutropenia are predictors of candidemia.